2013
DOI: 10.1371/journal.pgen.1003785
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-17-92, a Direct Ap-2α Transcriptional Target, Modulates T-Box Factor Activity in Orofacial Clefting

Abstract: Among the most common human congenital anomalies, cleft lip and palate (CL/P) affects up to 1 in 700 live births. MicroRNA (miR)s are small, non-coding RNAs that repress gene expression post-transcriptionally. The miR-17-92 cluster encodes six miRs that have been implicated in human cancers and heart development. We discovered that miR-17-92 mutant embryos had severe craniofacial phenotypes, including incompletely penetrant CL/P and mandibular hypoplasia. Embryos that were compound mutant for miR-17-92 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 42 publications
2
69
0
Order By: Relevance
“…To determine the miR-17-92 expression pattern in heart, we generated an miR-17-92 bacterial artificial chromosome transgenic LacZ reporter line (20) and compared it with a Pitx2 LacZ knock-in allele (16). In E12.5 hearts, LacZ staining indicated that miR-17-92 is expressed in the outflow tract (OFT), left atrium (LA), coronary sinus, and atrioventricular canal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the miR-17-92 expression pattern in heart, we generated an miR-17-92 bacterial artificial chromosome transgenic LacZ reporter line (20) and compared it with a Pitx2 LacZ knock-in allele (16). In E12.5 hearts, LacZ staining indicated that miR-17-92 is expressed in the outflow tract (OFT), left atrium (LA), coronary sinus, and atrioventricular canal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several reports have given an illustration of the differential expression of tissue miRNAs in murine upper lip [8], specific role of miRNAs in mouse embryos craniofacial morphogenesis [7,23]. Additionally, SNPs in the miRNA-binding sites were reported to be associated with non-syndromic orofacial clefts susceptibility [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies revealed that tissue miRNAs could be functionally important in regulating vertebrate and mammalian orofacial clefting [6][7][8]. However, there is little information available on the roles of specific miRNAs in human cleft lip.…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic orofacial tissues from wild-type mice at stages E10.5-E11.5 were dissected for Yap ChIP analysis, as previously described (Wang et al, 2013;Morikawa et al, 2015). Normal mouse IgG was used as a replacement control for the anti-Yap ChIP assay to show nonspecific immunoprecipitation of the chromatin.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%